U–Pb zircon geochronology of the Daraban leucogranite, Mawat ophiolite, Northeastern Iraq: A record of the subduction to collision history for the Arabia–Eurasia plates. (21st March 2017) - Mohammad, Yousif O.; Cornell, David H.
Abstract: The Mawat ophiolite is part of the Mesozoic Neo‐Tethyan ophiolite belt of the Middle East and is located in the Zagros Imbricate Zone of Iraq. It represents fossil fragments of the Neo‐Tethyan oceanic lithosphere within the Alpine collisional system between the Arabian and Eurasia Plates. The first U–Pb zircon dating of the Daraban leucogranite from the Mawat ophiolite provides a 207 Pb– 206 Pb age of 96.8 ± 6.0 Ma. The age is 59.0 ± 6.0 m.y. older than the previously published age of the Daraban leucogranite obtained by 40 Ar– 39 Ar muscovite dating method. The U–Pb dating of magmatic zircons collected from the Daraban leucogranite, which intrudes into the Mawat ophiolite, reveals that melting of the pelagic sediment beneath the hot Zagros proto‐ophiolite in an intra‐oceanic arc environment led to anatexis at the subduction front and the generation of granitic melts at 96.8 ± 6.0 Ma, which were emplaced in the overlaying mantle wedge. This process was a response to the initial formation of the Neo‐Tethys ophiolite above a northeast‐dipping intra‐oceanic subduction zone at 96.8 ± 6.0 Ma. Published 40 Ar– 39 Ar muscovite dating from the same leucogranite dike yields plateau ages of 37.7 ± 0.3 Ma, reflecting that the age was reset during the Arabia–Eurasia continental collision. Therefore, the bimodal age populations from the granitic intrusion in the Mawat ophiolite preserve a record of the subduction to the collision cycle of the Zagros Orogenic Belt. The 59.0 ± 6.0 m.y. age difference from the Daraban leucogranite represents the duration of the subduction‐collision cycle of the Zagros Orogenic Belt in the Kurdistan region of Iraq and the time span for the closure of the Neo‐Tethys Ocean along the northern margin of the Arabian plate. Abstract : Mawat ophiolite represents fossil fragments of the Neo‐Tethyan oceanic lithosphere within the Alpine collisional system between the Arabian and Eurasia Plates. The first U–Pb zircon dating of the Daraban leucogranite from the Mawat ophiolite provides a 207 Pb– 206 Pb age of 96.8 ± 6.0 Ma.